A Secret Hidden in the Sediments: Lepidoptera Scales - Montoro Girona, Miguel; Navarro, Lionel; Morin, Hubert (Frontiers in Ecology and Evolution, 2018)
Natural disturbance is one of the major topics in ecology. However, most paleoecological studies have only considered the influence of wildfire as an agent of disturbance, with fire history based primarily on the use of charcoal as a proxy for fire events. The frequency and intensity of insect outbreaks and their effect on the forest landscape have been neglected due to the absence of an effective proxy tool. Finding indicators able to provide insight into the impacts of past insect outbreaks is therefore essential. Fossil moth (Lepidoptera) wing scales offer a new approach for interpreting past insect-related disturbances and assessing the interactions between climate, fire and insect outbreaks. Paleoindicators must respond to three main criteria: 1) be in high abundance, 2) allow for easy identification and 3) remain well-preserved in sediment records. We demonstrate that wing scales are abundant in the boreal forest during insect outbreak periods. We also show that due to their chitin composition, these scales remain well-preserved throughout a 10,000-year sediment record. Furthermore, they are relatively easy to identify after being recovered from lake sediments. Therefore, we introduce the needs, potential and applications of this paleoindicator in forest ecology, and the main directions for the future research. This new approach offers an important scientific advance in forest ecology through a much improved, higher resolution reconstruction of an important natural disturbance.